A New Trend in Clinical Exercise Physiology - Exercise in End Stage Renal Disease: 臨床運動生理新趨勢 - 運動與末期腎病 - LEUNG, Raymond W. M. (Asian Journal of Physical Education & Recreation, 1999)
LANGUAGE NOTE | Document text in English; abstract also in Chinese. Research in exercise physiology achieved significant progresses in the past two decades. Clinical exercise physiology is a branch of exercise physiology in its proliferation phase. Research in clinical exercise physiology requires the collaboration between exercise physiologists and physicians, thus imposing newer challenges in this field. The present article will shed light on the potential research issues regarding clinical exercise physiology particularly in the renal area. 過去的二十年，運動生理的研究有重大的進展。臨床運動生理的研究替運動生理學開拓了新的領域。它需要運動生理學者與臨床醫生的緊密合作，本文嘗試綜合報道運動與腎病在臨床運動生理方面的突破性發展。